Analisis Latihan Kosakata dalam Buku Ajar Netzwerk A1 - Juanita Marchella, - (2020)
The proficiency of the four language skills, which consists of listening, speaking, reading and writing, can not be separated from vocabulary acquisition. Vocabulary acquisition should be supported by a good teaching method and practice, therefore the students can be certain with their understanding of the meaning of the words. However in the reality, learners still experience the difficulties in vocabulary learning, such as difficulties in understanding the meaning of a word or remembering the vocabulary in long-term memory. A solution that can be applied is to ascertain the teaching material to optimize vocabulary learning. The teaching material used as data source in this study is the textbook Netzwerk A1. The objectives of this study aims to find out: 1) the range of the vocabulary topics. 2) the phases of vocabulary teaching. 3) the support of vocabulary exercises for storing the vocabulary in long-term memory. This study used qualitative method, in particular descriptive analysis. The range of vocabulary topics is analyzed based on the theory from Glaboniat et al. Moreover, the theory from Lundquist-Mog and Widlok is used to analyze the phases of vocabulary teaching. The support of vocabulary exercises for storing the vocabulary in long-term memory is analyzed based on the theory from Apeltauer. The result of the analysis from the vocabulary exercises in the textbook Netzwerk A1, namely 18 exercises in the coursebook and 20 exercises in the workbook showed: 1) The textbook Netzwerk A1 contains 9 of the 15 vocabulary topics of Glaboniat et al. with the appearance of 21 times in the coursebook and 22 times in the workbook. 2) There are 5 phases of vocabulary teaching, namely 48 times in the coursebook and 59 times in the workbook. 3) There are 8 forms of the support of vocabulary exercises for storing the vocabulary in long-term memory, namely 57 times in the coursebook and 59 times in the workbook. The results of the analysis illustrated that the vocabulary exercises in the Netzwerk A1 textbook contain the range of vocabulary topics, the phases of vocabulary teaching, and the support of vocabulary exercises for storing the vocabulary in long-term memory, the number of which are varied, therefore they could be used by students and teachers to optimize vocabulary learning.